Makna Aksesoris Patung Bunda Maria di Kapel Graha Annai Velangkanni Medan - Rani Mardinata Sinambela; Tetty Mirwa (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the meaning and description of the accessories for the statue of the Virgin Mary in the Chapel of the Graha Annai Velangkanni. The sampling technique used in this research is total sampling, which is a whole sampling technique, so the samples in this study are 11 accessories worn on the statue of the Virgin Mary. The results of this study indicate that the accessories on the statue of the Virgin Mary still show the impression of mixing Indian culture with the Catholic Church. For the accessories of the statue of the Virgin Mary, the aesthetic value has aesthetic value, it can be seen in the form of the sculpture itself which has a good composition and a harmonious combination of colors according to the visual elements contained in the fine art. Types of accessories worn on the statue of the Virgin Mary has its own meaning, this can be seen in the use of accessories. There are 11 accessories worn on the statue of the Virgin Mary, namely: 12 Sea Stars (a sign of hope), the Golden Crown of Our Lady (a sign of the glory of a mother's heart), the Golden Crown of Jesus (a sign of prosperity), a Stola (a holy and clean symbol), the Pastor's Staff. (symbol of directing), Mangalsutra Necklace (symbol of love), Ring of Our Lady (symbol of dignity), Rosary (meditation instrument), Indian Flower Necklace (sign of respect), Saree (Indian traditional dress), and Crescent Moon (snake tread) .